Review and phylogeny of the New Zealand hagfishes (Myxiniformes: Myxinidae), with a description of three new species. (14th May 2015) - Zintzen, Vincent; Roberts, Clive D.; Shepherd, Lara; Stewart, Andrew L.; Struthers, Carl D.; Anderson, Marti J.; McVeagh, Margaret; Noren, Michael; Fernholm, Bo
Abstract: Hagfishes from New Zealand are reviewed and a phylogeny proposed using morphological and genetic data (DNA sequences of cytochrome c oxidase subunit I gene, COI, and the small subunit RNA, 16S ). Eptatretus cryptus sp. nov. was previously confused with Eptatretus cirrhatus (Forster in Bloch & Schneider, 1801) because of their similar morphology, and is found from the Three Kings Islands to Stewart Island and in the eastern part of the Chatham Rise (at depths of 96–922 m). Eptatretus poicilus sp. nov. is endemic to the Three Kings Islands, where it is common and associated with soft sediment and deep-sea coral-sponge habitats (114–842 m). Neomyxine caesiovitta sp. nov. is a slender hagfish found along the east coast of the North Island south to the Chatham Rise (430–1083 m). A neotype is erected for E . cirrhatus (type locality: Breaksea Sound, Fiordland), occurring widely in New Zealand coastal, shelf, and slope waters (1–922 m), but not at the Three Kings Islands. Eptatetrus goliath Mincarone & Stewart, 2006, Neomyxine biniplicata (Richardson & Jowett, 1951), and Nemamyxine elongata Richardson, 1958 are further described using additional material. Rubicundus eos (Fernholm, 1991) is still only known from the holotype (type locality: Challenger Plateau). Genetic results showed that the New Zealand Eptatretus species form a monophyletic group within the subfamily Eptatretinae, indicating likely speciation from a single common ancestor within the area. Eptatretus poicilus sp. nov. is the sister species of E . cirrhatus, and E . cryptus sp. nov. is closely associated with the clade formed by these two species. Eptatretus goliath is most closely associated with Eptatretus minor Fernholm & Hubbs, 1981 (Gulf of Mexico), these two species basally diverging within New Zealand hagfishes. The endemic genus Neomyxine forms a well-supported monophyletic group of as yet uncertain position within the phylogenetic tree. A key to the New Zealand hagfishes, fresh colour photographs, distribution maps, and in situ video recordings are presented.